2015
DOI: 10.3348/kjr.2015.16.5.1086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multi-Echo Dixon Methods with Volume Interpolated Breath-Hold Gradient Echo Magnetic Resonance Imaging in Fat-Signal Fraction Quantification of Paravertebral Muscle

Abstract: ObjectiveTo assess whether multi-echo Dixon magnetic resonance (MR) imaging with simultaneous T2* estimation and correction yields more accurate fat-signal fraction (FF) measurement of the lumbar paravertebral muscles, in comparison with non-T2*-corrected two-echo Dixon or T2*-corrected three-echo Dixon, using the FF measurements from single-voxel MR spectroscopy as the reference standard.Materials and MethodsSixty patients with low back pain underwent MR imaging with a 1.5T scanner. FF mapping images automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…However, it is well known that there are so many confounding factors in the calculation of fat or water signals by chemical shift‐encoded MRI, including main magnetic field inhomogeneity effects, the presence of multiple peaks in the fat spectrum, T2* effects, T 1 effects, eddy current effects, and the presence of susceptibility‐induced fat resonance shifts . Among them, T2* signal decay is particularly important in the fat quantification of bone marrow because trabecular bone, in general, shortens the T2* of water and fat components, inducing the confounded separation of fat and water signals . The multiple spectral peaks of fat are another large issue in fat quantification using chemical shift‐encoded MRI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is well known that there are so many confounding factors in the calculation of fat or water signals by chemical shift‐encoded MRI, including main magnetic field inhomogeneity effects, the presence of multiple peaks in the fat spectrum, T2* effects, T 1 effects, eddy current effects, and the presence of susceptibility‐induced fat resonance shifts . Among them, T2* signal decay is particularly important in the fat quantification of bone marrow because trabecular bone, in general, shortens the T2* of water and fat components, inducing the confounded separation of fat and water signals . The multiple spectral peaks of fat are another large issue in fat quantification using chemical shift‐encoded MRI.…”
Section: Discussionmentioning
confidence: 99%
“…With recent technical advancements, various chemical shift‐based water–fat separation methods, eg, Dixon methods, have been used to provide the distinctive separation of water and fat by correcting such confounding factors . The FF estimated from these methods is expected to improve the diagnostic performance of chemical shift‐encoded shift MRI in the differentiation of benign from malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For both uncompensated and compensated complex images, fat quantification was performed using T2*-IDEAL technique with 6 echoes (8) We used six echoes for both T2* and fat fraction rather than three echoes because previous studies have shown the improved fat fraction estimation when six-echo is applied in GRE-based fat quantification (14)(15)(16). Assuming identical T2* decay for both water and fat, the signal from a voxel including water and fat can be represented as:…”
Section: Methodsmentioning
confidence: 99%